Keanekaragaman dan Prevalensi Bakteri Pada Karapas Cuora amboinensis (Riche in Daudin 1801) Asal Habitat Alam - Rahaditiya, Mochammad Viekha; Tantu, Fadly Yasin; Nilawati, Jusri (Mitra Sains, 2022)
The aim of this research is to identify the diversity of bacterial types and determine the prevalence value of these bacteria on the carapace of C. amboniensis from natural habitats to support the provision of data that can later be used to support captive management activities and conservation actions C. amboniensis was collected manually and 20 individuals were obtained, samples were caught in December 2019. Data from bacterial identification was then used to calculate the prevalence of bacterial diversity. The identification results showed that there were 7 types of bacteria, most of which were Gram negative bacteria. The prevalence values were then calculated to obtain the results of A. caviae (5%), C. jejuni (30%), C. freundii (15%). ), F. breve (25%), L. monocytogenes (15%), P. haemolytica type A (5%), and P. alcaligenes (5%).